Implementing health policies in Australian junior sports clubs: an RCT - Tara Clinton-McHarg; Sharleen Gonzalez; Sharin Milner; Shauna Sherker; Melanie Kingsland; Christophe Lecathelinais; Alix Hall; Chris Doran; John Wiggers; Luke Wolfenden (BMC, 2019)
Abstract Background This pilot study aimed to test the potential effectiveness and acceptability of an intervention to support the implementation of 16 recommended policies and practices to improve the health promotion environment of junior sporting clubs. Reported child exposure to health promoting practices at clubs was also assessed. Methods A cluster randomised trial was conducted with eight football leagues. Fourty-one junior football clubs belonging to four leagues in the intervention group received support (e.g. physical resources, recognition and rewards, systems and prompts) to implement 16 policies and practices that targeted child exposure to alcohol, tobacco, healthy food and beverages, and participation in physical activity. Thirty-eight clubs belonging to the four control group leagues did not receive the implementation intervention. Study outcomes were assessed via telephone interviews with nominated club representatives and parents of junior players. Between group differences in the mean number of policies and practices implemented at the club level at follow-up were examined using a multiple linear regression model. Results While the intervention was found to be acceptable, there was no significant difference between the mean number of practices and policies reported to be implemented by intervention and control clubs at post-intervention (Estimate − 0.05; 95% CI -0.91, 0.80; p = 0.90). There was also no significant difference in the proportion of children reported to be exposed to: alcohol (OR 1.16; 95% CI 0.41, 3.28; p = 0.78); tobacco (OR 0.97; CI 0.45, 2.10; p = 0.94); healthy food purchases (OR 0.49; CI 0.11, 2.27; p = 0.35); healthy drink purchases (OR 1.48; CI 0.72, 3.05; p = 0.27); or participation in physical activity (OR 0.76; CI 0.14, 4.08; p = 0.74). Conclusions Support strategies that better address barriers to the implementation of health promotion interventions in junior sports clubs are required. Trial registration Retrospectively registered with the Australian New Zealand Clinical Trials Registry (ACTRN12617001044314).